Accessing and engaging women from socio-economically disadvantaged areas: a participatory approach to the design of a public health intervention for delivery in a Bingo club - Josie M. M. Evans; Gemma Ryde; Ruth Jepson; Cindy Gray; Ashley Shepherd; Dionne Mackison; Aileen V. Ireland; Marion E. T. McMurdo; Brian Williams (BMC, 2016)
Abstract Background Our aim was to use participatory methods to investigate the feasibility and acceptability of using Bingo clubs for the design and delivery of an evidence-based physical activity and/or healthy eating intervention to socio-economically disadvantaged women. This paper describes the participatory process that has resulted in a physical activity intervention for women aged >55 years, ready for pilot-testing in a Bingo club setting. Methods Studies using different quantitative and qualitative approaches were conducted among customers and staff of a Bingo club in a city of 85,000 inhabitants in central Scotland. These were designed to take the views of different stakeholders into account, with a view to enhancing uptake, engagement and effectiveness with any proposed intervention. Results Sixteen relevant studies were identified in a literature review that generated ideas for intervention components. A questionnaire completed by 151 women in the Bingo club showed that almost half (47 %) aged >55 years were not meeting physical activity guidelines; evidence backed up by accelerometer data from 29 women. Discussions in six focus groups attended by 27 club members revealed different but overlapping motivations for attending the Bingo club (social benefits) and playing Bingo (cognitive benefits). There was some scepticism as to whether the Bingo club was an appropriate setting for an intervention, and a dietary intervention was not favoured. It was clear that any planned intervention needed to utilise the social motivation and habitual nature of attendance at the Bingo club, without taking women away from Bingo games. These results were taken forward to a 5-h long participative workshop with 27 stakeholders (including 19 Bingo players). Intervention design (form and content) was then finalised during two round table research team meetings. Conclusions It was possible to access and engage with women living in areas of socio-economic disadvantage through a Bingo club setting. A physical activity intervention for women >55 years is realistic for recruitment, will address the needs of potential recipients in the Bingo club, appears to be feasible and acceptable to club members and staff, and has been designed with their input. A pilot study is underway, investigating recruitment, retention and feasibility of delivery.